THE RELATIONSHIP BETWEEN SELF-CARE MANAGEMENT AND QUALITY OF LIFE IN DIABETES MELLITUS PATIENTS IN IBNU SINA GRESIK HOSPITAL - Dalilah, Khairana Atikah; Okviasanti, Fanni; Purwanto, Cucuk Rahmadi (Universitas Airlangga, 2022)
Introduction: Non-adherence to self-care is often found in diabetes mellitus (DM) patients. Non-compliance in DM patients in performing self-care can affect the quality of life of patients. This study aimed to explain the relationship between self-care management and the quality of life of DM patients. Methods: This research design was analytically observational with a cross-sectional approach. The sample in this study was 80 respondents of DM patients treated at RSUD Ibnu Sina Gresik with a purposive sampling technique. They collected data using a questionnaire and statistical test of this study using the Spearman test. Results: The results are that the majority of self-care management is sufficient (67.5%) for as many as 54 people and good quality of life (86.2%) for as many as 69 people. The results of the correlation test using the spearman test obtained a p-value of 0.000 (p-value <0.05), and the correlation coefficient value is positive (r=0.479), which means that there is a significant relationship between self-care management and the quality of life of patients with diabetes mellitus in RSUD Ibnu Sina Gresik. Conclusions: Improved self-care management is associated with improving the quality of life of patients with diabetes mellitus in RSUD Ibnu Sina Gresik.